Chemical and Pharmacological Evaluation of Hulls of Prunus dulcis Nuts - Muhammad Nasimullah Qureshi; Sodik Numonov; Haji Akber Aisa (International Journal of Analytical Chemistry)
Researchers have shown that the almond hulls, normally wasted after utilization of nuts, contain a number of biologically active compounds based on which the present study has been carried out. Focus is placed on the mass spectrometric determination of the analytes along with the estimation of total polyphenolic and total flavonoid contents in the 70% ethanol extract. After partitioning the 70% ethanol extract in hexane, chloroform, ethyl acetate, n-butanol, and water, all the extracts were evaluated for their antioxidant, antidiabetic, and antimicrobial activities. The results delivered total polyphenolic compounds as gallic acid equivalents (1% w/w) of the dried extract and total flavonoid contents as quercetin equivalents (0.2% w/w) of the dried extract. Mass spectrometric analysis resulted in the identification of 15 compounds containing various derivatives of (epi)catechin, chlorogenic acid, kaempferol, isorhamnetin and their glycosides, ursolic acid, amygdalactone, and benzoic acid derivatives. Antioxidant activity experiments showed that highest activity was found in n-butanol extract among the studied samples with IC50 value as 76.04 μg/ml, while hexane and chloroform extracts were active against the PTP1B enzyme with IC50 values 9.66 μg/ml and 37.95 μg/ml, respectively. Hexane and chloroform fractions were active against Staphylococcus aureus with the zone of inhibition diameter 9 mm and 12 mm, respectively.